2013
DOI: 10.1186/1472-6823-13-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased vertebral morphometric fracture in patients with postsurgical hypoparathyroidism despite normal bone mineral density

Abstract: BackgroundThe mechanism behind parathyroid hormone (PTH) activation of bone remodeling is intimately dependent on the time of exposure of bone cells to hormone levels. Sustained high PTH levels trigger catabolism, while transitory elevations induce anabolism. The effects of hypoparathyroidism (PhPT) on bone are unknown. The objective was to study the impact of PhPT on bone mineral density (BMD), on the frequency of subclinical vertebral fracture and on mandible morphometry.MethodsThe study comprised thirty-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 37 publications
6
51
4
1
Order By: Relevance
“…Despite the tendency for higher BMD, its impact on longer term fracture risk has not been established in thalassemia. Indeed, in a group of nonthalassemic patients with surgical hypoparathyroidism, there was an increased frequency of morphometric vertebral fractures (141).…”
Section: H Hypoparathyroidismmentioning
confidence: 99%
“…Despite the tendency for higher BMD, its impact on longer term fracture risk has not been established in thalassemia. Indeed, in a group of nonthalassemic patients with surgical hypoparathyroidism, there was an increased frequency of morphometric vertebral fractures (141).…”
Section: H Hypoparathyroidismmentioning
confidence: 99%
“…Mendonça and cols. (19) recently performed a small study assessing the impact of hypoparathyroidism on BMD, frequency of subclinical vertebral fracture, and mandible morphometry. This study evaluated 33 postmenopausal women, 16 of whom had hypoparathyroidism, and 17 of whom were healthy controls matched for age, weight and height.…”
Section: Fracturesmentioning
confidence: 99%
“…29 In keeping with the importance of PTH for maintenance of trabecular bone, an increased prevalence of subclinical vertebral fractures indicative of vertebral fragility has been reported in patients with hypoparathyroidism. 30 Fracture healing studies have not, however, been reported in patients with hypoparathyroidism.…”
Section: Anabolic Effectsmentioning
confidence: 97%